NANOTECHNOLOGY AND THE FOOD SECTOR: FROM THE FARM TO THE TABLE - Meetoo, Danny D (Emirates Journal of Food and Agriculture, 2017)
The science of nanotechnology (NT) has been hailed as the new industrial revolution representing a new frontier of the 21st century. Defined as the control of matter at an atomic or molecular scale of between 1 and 100 nm, NT has been predicted to have a significant impact on society. While maintaining leadership in the competitive food market and food processing industry, NT has the capability of breaking down and manipulating foods, a seed, chemical pesticides and food packaging at the nano-scale level; and in so doing, is driving a nano-food and farming revolution. Apart from its promise to address climate change NT holds the potential of meeting global hunger. Today, consumers demand fresh authentic, convenient and flavourful food products. The future of new products and processes will witness the prolongation of their shelf life and freshness, improving the safety and quality of foods. NT therefore has the potential to revolutionise the food industry. Furthermore, this technology can be applied to develop nano-scale materials, controlled delivery systems, contaminant detection and create nano-devices for molecular and cellular biology.